Antibiotics in the Modern Era: Challenges, Misuse, and the Fight Against Resistance - Satish Kumar Sarankar; Sushma Somkuwar (International Journal of Antibiotics, 2024)
Overuse and inappropriate use of antibiotics in human medicine, agriculture, and environmental pollution. It is one of the biggest public health risks of the 21st century. The discovery of new antibiotics slowdown and the emergence of multidrug-resistant (MDR) microorganisms has highlighted the urgent need to Creative approaches to fighting opposition. This review explores the current challenges in antibiotic use, the factors driving resistance, and the strategies being implemented to address these issues. We examine the role of antibiotics in modern medicine, highlighting their indispensable role in treating infections but also acknowledging the increasing risks associated with their misuse. unusual trade international travel and the misuse of antibiotics in agriculture. It greatly facilitates the spread of drug-resistant bacteria.The economic and scientific challenges hindering the development of new antibiotics are also discussed, along with emerging approaches to incentivize research and development. Key strategies for combating AMR include improving stewardship practices, implementing regulatory measures, and developing alternative treatments such as vaccines, antimicrobial peptides (AMPs), and AI-driven drug discovery. We also review innovative interventions like the use of phage therapy and immune modulators. The article highlights the importance of a multifaceted approach, combining regulatory frameworks, scientific innovation, and global collaboration to mitigate the threat of AMR. Case studies such as Denmark’s successful ban on growth promoters and MIT’s AI-driven discovery of halicin provide valuable insights into potential solutions. Despite the challenges, promising advancements offer hope for overcoming the AMR crisis, but global cooperation and sustained investment in research are essential for long-term success in combating resistant infections.
Keywords: Alternative therapies; Antibiotic discovery; Antibiotic misuse; Antibiotic stewardship; Antimicrobial resistance (AMR); Multidrug-resistant bacteria; global health